2011
DOI: 10.3748/wjg.v17.i48.5295
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus in upper digestive tract tumors from three countries

Abstract: Based on our results, we cannot deny the possibility of HPV16 involvement in the carcinogenesis of the esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 40 publications
1
50
4
Order By: Relevance
“…Similar trends were observed in ECs although the difference was not statistically significant. Among HPV-16 intratypes, there is one polymorphism in the sequence of the E6 probe at nucleotide 145, and the Asian-American variant harbors this nucleotide substitution (C to T) [33]. However, this polymorphism is unlikely to cause a difference in viral load because the copy number of HPV-16 in the Asian-American variant was similar to other intratypes except E-350G.…”
Section: Methods For Hpv Detectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar trends were observed in ECs although the difference was not statistically significant. Among HPV-16 intratypes, there is one polymorphism in the sequence of the E6 probe at nucleotide 145, and the Asian-American variant harbors this nucleotide substitution (C to T) [33]. However, this polymorphism is unlikely to cause a difference in viral load because the copy number of HPV-16 in the Asian-American variant was similar to other intratypes except E-350G.…”
Section: Methods For Hpv Detectionmentioning
confidence: 99%
“…the hybridization event) is amplified and ultimately visualized with one of the various available methodologies. The liquid-phase signal amplification method the Digene Hybrid Capture 2 (HC2) assay [58] (Qiagen, Gaithersburg, MD, USA), is the first Our studies showed that the HPV genome was detected in 56% and 19% of SCCs of the oral cavity and esophagus, respectively, in cases collected from Japan, Pakistan and Colombia and the HPV prevalence in both oral cancers (OCs) and esophageal cancers (ECs) did not significantly differ by country [33]. HPV16 was frequently integrated into the host genome in patients with OCs and ECs, however, the viral loads in these malignancies were much lower than those found in cancer of the cervix [33].…”
Section: Methods For Hpv Detectionmentioning
confidence: 99%
See 3 more Smart Citations